2015
DOI: 10.1002/elps.201500394
|View full text |Cite
|
Sign up to set email alerts
|

Activation energy associated with the electromigration of oligosaccharides through viscosity modifier and polymeric additive containing background electrolytes

Abstract: The activation energy related to the electromigration of oligosaccharides can be determined from their measured electrophoretic mobilities at different temperatures. The effects of a viscosity modifier (ethylene glycol) and a polymeric additive (linear polyacrylamide) on the electrophoretic mobility of linear sugar oligomers with α1-4 linked glucose units (maltooligosaccharides) were studied in CE using the activation energy concept. The electrophoretic separations of 8-aminopyrene-1,3,6-trisulfonate-labeled m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…In agreement with results reported by others, 26,52,53 decreasing the separation temperature increased the migration time of all of the N -glycan peaks (see Table S-2). A plot of the mobility versus temperature (Figure S-3) revealed nominal change in mobility below 23 °C.…”
Section: Resultssupporting
confidence: 92%
“…In agreement with results reported by others, 26,52,53 decreasing the separation temperature increased the migration time of all of the N -glycan peaks (see Table S-2). A plot of the mobility versus temperature (Figure S-3) revealed nominal change in mobility below 23 °C.…”
Section: Resultssupporting
confidence: 92%
“…The drop at G8 was probably due to the conformation change from random coil to well defined helical structure as was suggested earlier [39]. Nevertheless, this similar selectivity of the monolith for oligomers presenting a size higher than 2 glucose units (GU) and lower than 15 is therefore well suited for the glycoprotein-derived N-glycans since the size of most plasma glycoprotein N-linked sugars usually ranges from 4 to 15 GU [40].…”
Section: Imac Enrichment Of the Apts Labeled Maltooligosaccharide Laddermentioning
confidence: 75%
“…On the contrary, the presence of PEO in the BGE revealed lower active energy for larger maltooligosaccharides. Interestingly, the addition of an organic modifier to the PEO containing BGE somehow canceled the effect of PEO [86]. In brief, these inspiring studies showed the possibility of BGE being addictive in controlling the separation performance of glycan.…”
Section: Capillary Electrophoresismentioning
confidence: 99%